Polyimides as resin matrices for advanced composites - Wilson, D.
In less then twenty years advanced composites have become established as efficient high-performance structural materials and their use is expanding rapidly. A simple definition of a composite is a material consisting of any combination of fibres or particles in a common matrix.
Keywords: HIGH PERFORMANCE LIQUID CHROMATOGRAPHY; COMPOSITE LAMINATE; RESIN SYSTEM CURE; CYCLE INTERLAMINAR SHEAR STRENGTH